Effect of glyphosate on renal function: A study integrating epidemiological and experimental evidence - Lin Hu; Mingcong Chen; Xiaoran Xue; Mingyi Zhao; Qingnan He (Ecotoxicology and Environmental Safety)
Glyphosate, a widely used herbicide globally, has prompted concerns regarding its potential health impacts. This study aimed to explore the link between glyphosate exposure and renal function by combining NHANES, a zebrafish model, and metabolomics. A cross-sectional analysis of 2013–2014 NHANES data investigated the relationship between glyphosate exposure and renal function [albumin-to-creatinine ratio (ACR) and estimated glomerular filtration rate (eGFR)]. A subsequent zebrafish experiment was conducted to verify this association. Embryos (0.75 hpf–96 hpf) were exposed to different glyphosate concentrations dissolved in water (0, 30, 60, 90, 120 μg/mL). The underlying mechanism of the association between glyphosate and renal function was explored by the real-time quantitative polymerase chain reaction (RT-qPCR) and non-targeted metabolomics analysis [embryos (0.75 hpf–96 hpf) were exposed to 90 μg/mL glyphosate]. 1170 participants were enrolled in the NHANES study. The NHANES-based study found a positive association between glyphosate and ACR [0.07 (0.01, 0.13)]. Higher urinary glyphosate levels, particularly in the third quartile group, were negatively linked to eGFR [−3.72 (−5.98, −1.46)]. Further zebrafish experiments indicated that zebrafish exposed to 90 μg/mL glyphosate exhibited increased mortality rates, higher fluorescence intensity, up-regulated the havcr1 expression level, and cystic dilatation of the kidney. Non-targeted metabolomics analysis identified differential metabolites (e.g., 5-Hydroxyindole acetic acid) and pathways (e.g., ABC transporters) influenced by glyphosate. Glyphosate exposure is negatively associated with renal function in community adults. The damage to the kidneys caused by glyphosate may be mediated through the regulation of metabolic pathways, and the specific mechanisms require further experimental investigation.